2017
DOI: 10.1080/15384047.2017.1345388
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics and experience in the treatment of giant retroperitoneal liposarcoma: A case report and review of the literature

Abstract: Retroperitoneal liposarcoma (RPLS) is a rare tumor, especailly those over 20 kg that are called "giant liposarcoma," whose characteristics and treatments remain relatively unknown. Herein, we report a giant RPLS measuring 65 × 45 × 30 cm in diameter and 31 kg in weight, which we successfully performed complete excision through interdisciplinary cooperation. The patient had an uneventful postoperative course and was discharged without complications. Afterwards he underwent radiotherapy and had no evidence of tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…In their cohort of 500 patients with RPS, the median survival after an R0 resection was 103 months compared to 18 months after an R1 or R2 resection. In a review by Zeng et al., the long-term 5- and 10-year survival rates without complete resection were described as 16.7% and 8.0%, respectively 22 . This reaffirms the curative role of surgical excision of RPS.…”
Section: Discussionmentioning
confidence: 86%
“…In their cohort of 500 patients with RPS, the median survival after an R0 resection was 103 months compared to 18 months after an R1 or R2 resection. In a review by Zeng et al., the long-term 5- and 10-year survival rates without complete resection were described as 16.7% and 8.0%, respectively 22 . This reaffirms the curative role of surgical excision of RPS.…”
Section: Discussionmentioning
confidence: 86%
“…In another study, 3 and 5-year survival rates of patients who underwent complete resection were reported as 73% and 60%, respectively [10]. Long-term prognosis is poor in patients without complete resection and 5-, and 10-year survival rates are 16.7% and 8%, respectively [11].…”
Section: Discussionmentioning
confidence: 98%
“…However, chemotherapy has been suggested, but it has worsened patient's prognosis [10]. The effectiveness of postoperative radiotherapy has been inquired in local control rather than overall survival [11]. Ballo et al also stated that radiotherapy was ineffective in RPLS cases and radiotherapy applied may cause neuropathy, hydronephrosis, fistula and ileus [15].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, complete surgical resection is the cornerstone of non-metastatic RLS treatment. Furthermore, R0 resection is the most consistent prognostic factor [5] .…”
Section: Discussionmentioning
confidence: 98%